Enhancing Healthcare Professional Practice in the Philippines toward ASEAN Integration through the Continuing Professional Development Law - Crispino, Kevin T.; Rocha, Ian Christopher N. (ASEAN Journal of Community Engagement, 2021)
The Republic Act 10912, otherwise known as the Continuing Professional Development (CPD) Act of 2016, was passed into law to promote and upgrade the practice of healthcare professions in the Philippines. Since the establishment of the Association of Southeast Asian Nations (ASEAN) Economic Community (AEC), CPD has been considered an area of development through which Filipino professionals are trained to become globally competitive. The Philippine government upholds several agreements made among ASEAN member-states, including recognizing professionals in every ASEAN country, facilitating the mobility of professions within the region, exchanging expertise on standards and qualifications, promoting best practices, and providing valuable opportunities for the training and capacity building. This policy analysis paper evaluated the advantages and disadvantages of the new law in terms of enhancing the capability of professionals through CPD programs. Thus, this article identified the benefits and burden experienced by Filipino healthcare professionals since its enactment. To name a few, the advantages include improving professional competencies, acquiring and refining the necessary knowledge and skills for career advancement, achieving personal and professional growth, and becoming globally competitive while the disadvantages include high cost and expense, inaccessibility and unavailability of CPD programs, additional requirement despite the work overload, lack of support, time constraints among family and loved ones, and limitations of rest and relaxation. Policy directives in addressing these salient issues in the implementation of the law are also recommended. The CPD is indeed a critical factor in ensuring that Filipino healthcare professionals are empowered and globally competitive. In return, their societal contributions will benefit the country’s welfare and economic growth, continued development toward AEC and globalization, and community engagement within the ASEAN region through mobility.